The impact of beetroot juice supplementation on performance in endurance sports: A review of running, cycling, and swimming - Kubas, Wojciech; Sadok, Aleksandra; Białek, Aleksandra; Karczewski, Jakub; Niemcewicz, Wojciech Jan; Ryń, Kamila; Kożlicka, Aleksandra; Klajda, Jakub; Czerniakowski, Mikołaj; Gorczyca, Zuzanna (Quality in Sport, 2026)
Background. Dietary nitrate (NO3-) from beetroot juice (BRJ) enhances nitric oxide bioavailability via the NO3-, NO2-, NO pathway, which is particularly effective during high-intensity exercise. Aim. To evaluate the impact of BRJ on endurance performance in running, cycling, and swimming (2020–2025) and establish standardized dosing protocols. Material and methods. A systematic review of PubMed, Scopus, and Web of Science was performed, focusing on meta-analyses and RCTs assessing exercise economy (VO2), time-trial results, and recovery markers in recreational and elite athletes. Results. BRJ reduces submaximal oxygen cost by 1.5–5.0%. Recreational athletes exhibit a ~15.7% increase in time-to-exhaustion, while cyclists show power output improvements of 1.2–3.0%. Swimming-specific data indicate enhanced stroke efficiency and accelerated lactate clearance. Elite athletes require chronic loading (3–7 days) to overcome the "ceiling effect" associated with high baseline nitric oxide levels. Conclusions. BRJ is a safe and validated ergogenic aid. Optimal performance gains require a chronic protocol (>8 mmol NO3-/day) for 3–7 days, with specific focus on ingestion timing and preserving the oral microbiome.